Nathaniel's Ambition to Revenge on Simon Lovelace Discribed in Jonathan Stroud's The Bartimaeus Trilogy: The Amulet of Samarkand - Alfian Rheza Arjuna (Universitas Dian Nuswantoro, 2018)
This thesis is entitled Nathaniel's Ambition to Revenge on Simon Lovelace Described in Jonathan Stroud's The Bartimaeus Trilogy: The Amulet of Samarkand has an objective to analyze ambition and motive of Nathaniel alias John Mandrake to revenge on Simon Lovelace as his enemy. The researcher used descriptive qualitative method to find out Ambition and motive of Nathaniel alias John Mandrake after Humiliated by Simon Lovelace. While library research method was used to gain any references dealing with the object of analysis. Technique of analysis is divided into two, there are structural and psychology approach. Structural approach was used to analyze structural elements like general description, conflict, and setting, while psychological approach was used to analyze and describe problems dealing with the object of study. The collected data were analyzed by reading the novel. The researcher presents all the data by the quotation through general description, conflict and setting. The results of this research show that the main character is described as a person who is genius, clever, restless, arrogant, and curious. He belongs to round dynamic character since he has more than one specific traits and he also changes from the beginning till the end of the story. The main character also experiences internal conflict about him admitting the truth about who steal the amulet, to disobey his master, blame himself and also external conflict against his master, Bartimaeus, Maurice Schyler, The Resistance and Simon Lovelace. The setting in this novel is divided into setting of place; Attic room, Sir Underwood house, Boarded-up building, Heddleham Hall, Small library and The hall of Heddleham Hall, setting of time; morning in boarded-up building, 10.15 am and setting of social on high social class. Nathaniel alias John Mandrake's ambition is motivated by humiliation and murder drives him to gain everything that needs to commit revenge. Living as magician which is always surrounded by ambition and domination, losing someone that he loves, humiliated and be degraded by other. Keywords: Ambition, Amulet of Samarkand, Jonathan Stroud, Motive, Revenge